TRAVELS IN SPACE AND PLACE: IDENTITY AND RURAL SCHOOLING - Corbett, Michael (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
This analysis draws on interview data from a three‐year study of educational decision making of youth living in a coastal community in Atlantic Canada. Students whose educational and mobility aspirations extend outside the known spaces of the community develop the ability to negotiate multiple social spaces in and out of school. The school‐successful ʺfloaterʺ identity position is assumed by youth comfortable in a variety of social groups and situations ranging from peer cliques to interactions with teachers and other institutional authority figures. This contrasts with more localized identity positions, marked by strong and exclusive identification with local networks. Key words: rural education, mobility, education trajectories, high school, school cliques, Nova Scotia education Dans cet article, l’auteur analyse les données tirées d’entrevues effectuées dans le cadre d’une étude de trois ans portant sur les décisions de jeunes d’une localité côtière du Canada atlantique quant à leurs études. Les élèves dont les aspirations en matière d’éducation et de mobilité dépassent les espaces connus de la communauté développent l’aptitude à négocier de multiples espaces sociaux à l’école et en dehors de l’école. Les jeunes qui sont à l’aise dans plusieurs groupes sociaux et situations, allant des cliques de camarades aux interactions avec les enseignants et autres figures d’autorité, adoptent la position du « migrant » qui réussit à l’école. D’autres, au contraire, s’identifient fortement et de manière exclusive à des cercles ou réseaux locaux. Mots clés : éducation rurale, mobilité, parcours scolaires, école secondaire, cliques d’élèves, enseignement en Nouvelle‐Écosse